2022
DOI: 10.1177/15248380221082081
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Child and Adolescent Cognitive Development: A Systematic Review

Abstract: Intimate partner violence (IPV) is a public health and human rights issue, with millions of children affected worldwide. While several reviews have explored the emotional-behavioural functioning of children exposed to IPV, this review aimed to examine the relationship between children's exposure to IPV and their cognitive development, and to identify associated factors such as aspects of parenting. The databases MEDLINE, PsycInfo, EMBASE, Family and Society Studies Worldwide, CINAHL, and ERIC were searched usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Num outro estudo, realizado pelos autores com filhos de mulheres vítimas de violência interparental acolhidas em casas abrigo, concluíram que 70% dessas crianças foram também elas vítimas de abuso ou negligenciadas -"pais fisicamente agressivos durante conflitos conjugais tendem, geralmente, a ser fisicamente agressivos durante conflitos pais-filhos" (Jouriles et al, 1987, p. 453); para conclusões similares, cf. Kertesz et al, (2021); Otaguiri et al, (2022); Savopoulos et al (2023). xi Revela-se importante sinalizar os avanços ocorridos em 2021 com o reconhecimento do estatuto de vítima às crianças que testemunhem ou vivam em contexto de violência interparental.…”
Section: Exposição Da Criança à Violência Interparental: Prevalência ...unclassified
See 2 more Smart Citations
“…Num outro estudo, realizado pelos autores com filhos de mulheres vítimas de violência interparental acolhidas em casas abrigo, concluíram que 70% dessas crianças foram também elas vítimas de abuso ou negligenciadas -"pais fisicamente agressivos durante conflitos conjugais tendem, geralmente, a ser fisicamente agressivos durante conflitos pais-filhos" (Jouriles et al, 1987, p. 453); para conclusões similares, cf. Kertesz et al, (2021); Otaguiri et al, (2022); Savopoulos et al (2023). xi Revela-se importante sinalizar os avanços ocorridos em 2021 com o reconhecimento do estatuto de vítima às crianças que testemunhem ou vivam em contexto de violência interparental.…”
Section: Exposição Da Criança à Violência Interparental: Prevalência ...unclassified
“…Tendo presente, a importância da cognição para "o processamento emocional, o desenvolvimento e a manutenção da saúde e das relações, o sucesso escolar", entre outros, facilmente concordamos que quando essa função é comprometida por experiências traumáticas, as consequências são profundas para a vida quotidiana das crianças (Savopoulos et al, 2023(Savopoulos et al, , p. 1883. Estes autores, dão conta de que 26 estudos, dos 38 revistos, estabeleceram uma associação significativa entre a exposição à violência interparental e a existência de défices nas crianças ao nível das suas competências cognitivas.…”
Section: Consequências Da Exposição à Violências Para O Desenvolvimen...unclassified
See 1 more Smart Citation
“…The association between resources at home for child stimulation, including available play materials and stimulation activities with any adult person in the home, defined as the quality of the home environment, and cognitive development has been well documented in LMICs (Hamadani et al, 2010; Rubio‐Codina & Grantham‐McGregor, 2020). Parental, but more specifically maternal, characteristics were also found to be important for child development, including maternal education (Jeong et al, 2017), intimate partner violence against the mother (Savopoulos et al, 2022), and maternal depression (Liu et al, 2017). A recent study conducted in Brazilian municipalities among children less than 3 years old revealed that children were more likely to meet early childhood development milestones if they were not born with low birth weight, were exposed to (manufactured) toys in their house, their heads of household were employed, their caregivers had read the Child Health Handbook, and engaged them in stimulating activities (Venancio et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It can occur in any relationship regardless of gender or sexual orientation, although women, transgender and gender non-binary persons are at increased risk of experiencing IPV. It is widely acknowledged that children’s exposure to DVA is widespread and can lead to serious and long-term negative consequences, stretching across all domains of health and development ( 3 6 ). This has resulted in government policies to ensure that health and social care services respond to and safeguard children (and their families) who might be at high risk of or have experienced DVA ( 7 – 10 ) However, there is scant high-quality evidence about which interventions are effective and for whom, in which circumstances ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%